2009
DOI: 10.1186/1472-6939-10-18
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of euthanasia and physician-assisted suicide in the Netherlands: descriptive study

Abstract: BackgroundAn important principle underlying the Dutch Euthanasia Act is physicians' responsibility to alleviate patients' suffering. The Dutch Act states that euthanasia and physician-assisted suicide are not punishable if the attending physician acts in accordance with criteria of due care. These criteria concern the patient's request, the patient's suffering (unbearable and hopeless), the information provided to the patient, the presence of reasonable alternatives, consultation of another physician and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 25 publications
1
63
0
1
Order By: Relevance
“…There might also be a lack of recognition of all types of suffering in healthcare, where physicians prefer to see physical suffering as a more legitimate form of intolerable suffering [7][8][9]. According to a Norwegian study, physicians were observed to use strategies to readdress their patients' concerns into a medical context, while their existential meanings were removed and neglected [37].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…There might also be a lack of recognition of all types of suffering in healthcare, where physicians prefer to see physical suffering as a more legitimate form of intolerable suffering [7][8][9]. According to a Norwegian study, physicians were observed to use strategies to readdress their patients' concerns into a medical context, while their existential meanings were removed and neglected [37].…”
Section: Discussionmentioning
confidence: 96%
“…However, there are no clear definitions of what constitutes intolerable suffering [6], which makes its assessment by physicians subjective. Previous studies in the Netherlands have shown that physicians vary in their assessment of suffering, and that there seems to be a preference for judging physical suffering as intolerable rather than suffering from other dimensions [7][8][9].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is obvious that eyes will be directed at the outcomes of research in the Netherlands. EAS is permitted if the criteria for due care are met 6,12 and these include unbearable and hopeless suffering, no realistic alternatives for treatment, a well-considered voluntary request, having informed the patient about his or her situation and prospects, consultation by an independent physician and a prudent performance of EAS. Successive studies, using data from death certificates and questionnaires directed at physicians, generated important information.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Requests for EAS are directed at physicians, mainly by end-of-life cancer patients in primary care. [4][5][6] In many countries, relevant proportions of end-of-life cancer patients are cared for in primary care. [7][8][9] Requests by patients, directed at physicians to end their lives, touch the fundamental questions about the nature of suffering, the meaning of life and the goals of medicine.…”
Section: Introductionmentioning
confidence: 99%